Perbandingan Tingkat Efisiensi Biaya Produksi Penggilingan Padi Tetap dan Bergerak di Kecamatan Sukodadi Kabupaten Lamongan: Comparasion of The Level of Production Cost Efficiency - Permana, Dafid; Winarno, Sri Tjondro; Syah, Mirza Andrian (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2025)
Indonesia's dependence on rice makes the rice milling process a sector that is highly sensitive to changes in costs and supply dynamics. Amid frequent fluctuations in grain prices that are often not balanced with rice prices, rice milling businesses face increasingly complex cost pressures, including UD. Hasil Bumi, which operates in Lamongan Regency. This study formulates two main focuses, namely analyzing the level ofprofitability of rice milling businesses and evaluating the cost efficiency ofproduction by making comparisons with mobile rice millsthat have different working systems.. The study was conducted using a descriptive quantitative approach through the collection of operational data during 20 production processes in May 2025. The results of the study show that fixed rice mills produce greater production volumes and revenues, but the proportion of costs incurred is also much greater. Conversely, mobile rice mills have lower operating costs, resulting in higher cost efficiency. However, both rice mills are classified as efficient (Eb > 1). However, the P Value in the statistical test is below 0.05, indicating a significant difference between the two. These findings illustrate that mobility and simplicity of cost structure give mobile rice mills an advantage, while stationary rice mills offer advantages in terms of capacity and product quality. Overall, this study emphasizes the importance of more adaptive cost management strategies to optimize profits in unstable market conditions. Keyword: Cost, Efficiency, Production, Profit, Revenue.